A Students’ Perspective on University Education and Well-Being One-Year into the COVID-19 Pandemic - Akira Gareeb; Isabella Gavazzi; Natasha Woodman; Chulananda Goonasekera; Antoinette Lombard; Mohammad Omar Faruq; Joanna Ray; Rasika Dhanapala; Sadhani Sandarenu; Mosarrat Mahjabeen; Seema Hashmi; Darshana Kottahachchi; et al. (International Journal of Medical Students, 2022)
We report university student perspectives on COVID-19 impact on education, general health and well-being, one year into the pandemic.